Mediation of Job Satisfaction on Employee Performance Through Influence Incentives and Organizational Commitment: A Study of Islamic Economics and Business Baitul Maal Hidayatullah, Banten Province - Mutiasari, Bela; Prahiawan, Wawan; Rosyid, Abdul; Imron, Ali; Hilaldi, Dika (Journal of Modern Islamic Studies and Civilization, 2025)
This study investigates the influence of incentives and organizational commitment on employee performance, with job satisfaction as a mediating variable. The research was conducted at Baitul Maal Hidayatullah (BMH) Banten Province, a non-profit organization engaged in zakat, infaq, and sadaqah management. The study employed a quantitative method with a saturated sample of 100 employees. Data were collected through questionnaires and analyzed using Structural Equation Modeling with SmartPLS 4.0. The results reveal that both incentives and organizational commitment have a significant and positive impact on job satisfaction and employee performance. Furthermore, job satisfaction significantly enhances employee performance and partially mediates the relationship between organizational commitment and performance. However, its mediating effect between incentives and performance is not significant. These findings underscore the critical role of intrinsic factors such as commitment and satisfaction in improving performance, especially in non-profit organizational contexts.